Exploring the Relationship Between Social Anxiety Concerning Appearance and the Economic Implications of TikTok’s Beauty Filters among Female Athletes in China - Yufei Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This research delves into the intricate nexus between social anxiety related to physical appearance and the economic advantages derived from the utilization of TikTok's Beauty filter among female athletes in the realm of sports. The burgeoning presence of social media platforms, including TikTok, has not only transformed the way individuals engage online but has also redefined how female athletes perceive and present themselves within the digital sphere. Social anxiety pertaining to physical appearance is a pervasive concern that can exert a substantial influence on the online interactions of female athletes. The Beauty filter, a prominent feature on TikTok, permits users to digitally enhance their facial attributes and overall appearance. Through an extensive review of existing literature and the application of both qualitative and quantitative research methods, this study aims to illuminate the intricate interconnections between these phenomena. It seeks to comprehend how social anxiety may drive the adoption of beauty filters as a coping mechanism among female athletes, potentially affecting their self-esteem and reliance on these digital enhancements. Furthermore, this research explores the extent to which the use of the Beauty filter can translate into economic benefits for female athletes in sports. It examines factors such as heightened engagement rates, amplified follower growth, and opportunities for monetization through brand collaborations and sponsored content. The study also acknowledges the influence of cultural nuances, recognizing that beauty standards can diverge markedly across regions and cultures. Chinese female athletes, for instance, may be influenced by distinctive beauty ideals that differ from Western standards, thereby shaping their perceptions of attractiveness and the economic rewards attainable through the use of such filters. This study underscores the imperative for additional research to deepen our comprehension of the multifaceted connection between social anxiety concerning appearance, the adoption of digital beauty filters, and the economic consequences for female athletes in sports leveraging TikTok. The insights gleaned from this inquiry can offer valuable contributions to the fields of sports psychology, social media studies, and sports marketing, offering a nuanced perspective on the intricate interplay between self-perception, digital technology, and economic success in the context of female athletes in sports amidst the era of social media."